2001
DOI: 10.1046/j.1351-0126.2001.00428.x
|View full text |Cite
|
Sign up to set email alerts
|

Fiction, poetry and mental health: expressive and therapeutic uses of literature

Abstract: People with experience as mental health clients, mental health nurses, writers and other professionals have used literature to benefit mental health service users in various ways. These include expressive writing, as well as applications in psychotherapy and counselling and to deal with specific problems and symptoms. In addition, therapeutic story-telling, bibliotherapy and poetry therapy have been used. Various benefits have been described, but some accounts do not include evidence of clinical effectiveness.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
64
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(65 citation statements)
references
References 27 publications
0
64
0
1
Order By: Relevance
“…Such books complement cognitive therapies, including therapeutic writing or journaling. These processes accelerate learning and increase treatment impact (Floyd, 2003;McArdle & Byrt, 2001). Another method involves the use of literature such as poems, short stories, and novels.…”
Section: Current Components Of Bibliotherapymentioning
confidence: 98%
“…Such books complement cognitive therapies, including therapeutic writing or journaling. These processes accelerate learning and increase treatment impact (Floyd, 2003;McArdle & Byrt, 2001). Another method involves the use of literature such as poems, short stories, and novels.…”
Section: Current Components Of Bibliotherapymentioning
confidence: 98%
“…13,14 Fiction is frequently recommended informally by library staff and shared with patients in reading groups along with poetry and play reading. The use of reading therapy could be developed with a more structured approach where clinicians working together with library staff and other health professionals introduce carefully selected material to aid the recovery of patients.…”
Section: Choice Of Subject Mattermentioning
confidence: 99%
“…It is also a wonderful way of expressing our inner thoughts. Studies have shown that poetry can be used very effectively to improve mental health [6]. Every one, in some manner, has a certain level of imagination and creativity to express himself in poetry.…”
Section: Why Generate Poetry By Sms?mentioning
confidence: 99%